Comparison of chemical profile and biological activities of different plant parts of Ficus deltoidea Jack var. trengganuensis - Khamsah Suryati, Mohd; Abd Jamil, Zakaria; Azierah, Azemin (2015)
Ficus deltoidea var. Trengganuensis (FDT) is one of the variety of a highly potential herbs, Ficus deltoidea Jack. This herb has pharmacologically been shown to possess numerous biological activities. Commonly, only leaves have been used medicinally. In order to assess whether other part such as fig and stem can also be used for medicinal purposes, chemical profile and biological activities were compared. Samples that consist of leaves, figs and stems were collected from four locations in Trengganu state, east coast of Peninsular Malaysia. Thin layer chromatography (TLC) and Fourier transform infrared (FTIR) were used to assess the chemical profile. Two compounds, vitexin and isovitexin were used as authentication marker of FDT. A good separation of the chemical components and marker in all sample with distinct spots observed on fig TLC chromatogram at the solvent system of ethyl acetate: formic acid (0.1%): methanol (4:6:2 v/v/v). FTIR fingerprints also exhibit different profile for fig, stem and leaf extract. Principle component analysis on FTIR data revealed that figs from four locations clustered into one group in positive PC2 quadrant suggest that fig has specific constituents, which discriminate them from leaf and stem. Biological activities were assessed by 2, 2-diphenyl-1- picrylhydrazyl (DPPH) inhibition and α-glucosidase inhibition assays. Comparison between plant parts discovered that figs from all locations have the highest inhibition on both activities compared to leaves and stems. Finding from this study revealed that figs of FDT could also be consumed for therapeutic purposes in addition to the leaves.